Effect Biopesticides of Fungi Entomopathogenic on the Damage Intensity of Edamame Soybean - Rahim, Abdul; Erwin, Erwin; Nurmaisah, Nurmaisah; Suyanto, Hari (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Biopesticides as an alternative to synthetic pesticides are rarely at the field testing level. The research described the composition of pest types and compared the intensity of plant pest attacks in edamame soybean cultivation areas. The study used a Randomized Block Design with biopesticide or entomopathogenic fungus treatments. The active ingredients consisted of L. lecanni, B. bassiana, and M. anisopliae, and the active ingredients were synthetic chemical compounds (control). Each treatment was repeated six times to obtain 24 experimental plots. The research analyzed growth and vegetative phases, pest composition, and intensity of pest attacks. Data analysis used the Kruskall-Wallis and Wilcoxon tests. The results showed that the control treatment had the highest plant height, number of productive branches, pods, and fresh seed. Furthermore, the pest composition comprises leaf-destroying pests: armyworms, grasshoppers, and pod-sucking ladybugs. The lowest level of leaf damage occurred two weeks after planting (MBS) on B. Bassiana plants. Meanwhile, M. anisopliae at 4 and 6 WAP, then L. lecanni at 8 WAP with damage of 16.69, 18.59, 20.88, and 20.24%, respectively. There were differences in leaf damage in the control and B. bassiana and M. anisopliae at 2 WAP. However, synthetic pesticides are more effective in suppressing pod damage than biopesticides. The findings of this research show that biopesticides are an alternative, but their effectiveness cannot exceed synthetic pesticides in edamame soybean cultivation.